Influence of pulse magnetic fields treatment on optical properties of GaAs based films - Konakova, R.V.; Sosnova, M.V.; Red’ko, S.M.; Milenin, V.V.; Red’ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Long-term transformations of the optical reflectance of GaAs epitaxial structure under weak magnetic field treatment (B = 60 mT, f = 10 Hz, τ = 1.2 ms, t = 5 min) have been obtained. Optical measurements were performed within the wavelength range 800…1100 nm at 300 K. Non-monotonous changes of reflectance were observed. Experimental results have been interpreted in terms of diffusion of point defects, resulting from destruction of metastable complexes (probably [VAs+impurity]), from the internal boundaries to the surfaces of the investigated structures. The method for detection of non-equilibrium complexes in multilayer objects has been proposed.